Can Managers Be Wrong and Still Be Right? An Examination of the Future Realization of Current Management Forecast Errors - Kimbrough, Michael D.; Lee, Hanna; Zheng, Yue (The Accounting Review, 2021)
ABSTRACT We examine whether management forecast errors (MFEs), which are traditionally interpreted as backward-looking indicators of how well forecasts preempted earnings announcements, also operate as forward-looking measures that aid with predicting future earnings. This possibility arises if an MFE represents unrealized revenues or expenses a manager originally anticipated to occur in the forecast period but that ultimately occur in subsequent periods. Consistent with this possibility, we document that optimistic MFEs contain incremental information over current earnings for predicting future earnings realizations. This finding does not extend to pessimistic MFEs, consistent with such errors reflecting expectations management. The predictive information in optimistic MFEs is negatively related to managers' incentives to intentionally bias the forecast and is positively related to managerial ability. Analysts' post-earnings announcement forecasts for the subsequent period overestimate the future realization of MFEs, but such overestimation is less severe when managers issue timely post-earnings announcement forecast revisions for subsequent periods. Data Availability: Data used in this study are publicly available from sources identified in the text. JEL Classifications: D80; G14; G17; M41.